Implementation of strategy instruction in teaching english as a foreign language: a systematic review - Su, Li; Noordin, Nooreen; Jeyaraj, Joanna Joseph (Tresorix, 2023)
Strategy instruction (SI) has played an essential role in English as a foreign language (EFL). Its usage looks to provide potential benefits for improving learners’ strategic competence for lifelong education. However, the current state of research on SI in EFL is fragmented and does not sufficiently elaborate upon the optimal conditions for effectively implementing SI. The present study aims to address this gap by synthesizing existing studies on SI in EFL and employing a systematic literature review using Petticrew and Roberts’ (2008) framework. The related 25 articles were selected from databases of Educational Resources Information Centre (ERIC), Scopus, and Google Scholar from 2010 to 2022. The findings indicated that Strategy-based Learning (SBL) is one of the most effective approaches for implementing SI. The factors impacting the effectiveness are also revealed. Finally, this study recommends that future studies should integrate self-regulation into SI research and that the collaborative approach should be conducted by scholars and educators to enhance the efficiency of IS.